Barrier Reduction of Lithium Ion Tunneling through Graphene with Hybrid Defects: First‐Principles Calculations (Adv. Theory Simul. 2/2018). Issue 2 (20th February 2018) - Xin, Yanbo; Huang, Anping; Hu, Qi; Shi, Hongliang; Wang, Mei; Xiao, Zhisong; Zheng, Xiaohu; Di, Zengfeng; Chu, Paul K.
Abstract : A Taiji yin‐yang fish is the crystallization of Chinese traditional culture. It illustrates the complementarity between perfection and flaw. In article number1700009, Anping Huang and co‐workers apply elastic band simulation to identify strategies to reduce the energy barrier height of Li ions tunneling through the perfect lattice of monolayer graphene sheets. They reveal that artificial defects can affect the distribution of electron clouds in the lattice, providing a possible path for ion migration.